OUTCOMES OF PATIENTS UNDERGOING PANCREATODUODENECTOMY (WHIPPLE’S PROCEDURE) ACCORDING TO THE PRESENCE OF PREOPERATIVE BILIARY DRAINAGE - Rómulo VARGAS-RUBIO; Ana Maria LEGUIZAMO-NARANJO; Oscar MUÑOZ-VELANDIA; Cristiam David PULGARIN-HERRERA; Carlos Ernesto LOMBO; Liliana CUEVAS-LOPEZ; Elio Fabio SANCHEZ; Francisco Javier HENAO (Arquivos de Gastroenterologia)
ABSTRACT Background: Pancreaticoduodenectomy is the procedure of choice for the treatment of resectable pancreaticoduodenal tumours. It has been proposed that jaundice is associated with worse outcomes, but the usefulness of preoperative biliary drainage in these patients is still controversial. Methods: Retrospective cohort study of patients undergoing Whipple procedure at the Hospital Universitario San Ignacio, Bogotá (Colombia), between January 2010 and June 2023. The cohort of patients who underwent preoperative biliary drainage was compared with those who went directly operated on. Comorbidities, functional status and procedural characteristics were recorded. The outcomes, including mortality and intraoperative and 30-day postoperative complications, were compared between groups. Results: A total of 98 patients were included, 49 of whom underwent preoperative biliary drainage. In this group, there was a higher proportion of patients with pathological stage II and III disease (77.5 vs 49.0, P=0.04) and higher preoperative bilirubin levels (median 6.4 vs 4.9 mg/dL; P=0.02). There were no differences in intraoperative (10.2% vs 14.3%; P=0.34) or postoperative (61.2% vs 51%; P=0.15) complications, but 30-day mortality was higher in patients with biliary drainage (8.2 vs 20.4%; P=0.03). Conclusion: Our data suggest that there are no differences in postoperative complications. The higher mortality rate in patients with preoperative biliary drainage may be related to differences in baseline patient characteristics and/or delays between biliary drainage and Whipple procedure.